Examining Collateral Prerequisites for Small and Medium-Sized Business Loans - Jrad, Majida (International Journal of Membrane Science and Technology, 2023)
This paper examines the factors that affect loan collateral specifically for SMEs in Lebanon, which is a country with a small, open emerging market economy. Collateral should secure the bank loan, but in practice it is adjusted according to other socio-economic criteria of the firms. This is especially true for SMEs and even more so for emerging countries. We propose in this research to illustrate the signals mobilized by banks when granting secured loans. The data on these variables come from the Lebanese Central Bank and the World Bank. They contain observations for two samples - 532 firms for 2019 and 561 firms for 2013. A set of factors influence the level of collateral required: those related to firm characteristics (relevant variables: age, size, audit of financial statements, provision of training to workers, private shareholder ownership, quality recognition, experiencing at least one bribe request, female manager), manufacturing (reflects economic sector), interest rate (reveals loan characteristics), and location in the capital (reveals loan market characteristics). The logistic regression estimates suggest that collateral required by older firms is higher even that SMEs have financial statement revised annually by external auditors. Size and interest rate contribute to lower collateral requirements. The consistency of results in the combined panel, 2013, and 2019 shows the reliability of the Lebanese Banking Sector norms and policies